Asymptotics for ultimate ruin probability in a by-claim risk model - Zhang, Aili; Liu, Shuang; Yang, Yang (Nonlinear Analysis: Modelling and Control, 2021)
This paper considers a by-claim risk model with constant interest rate in which the main claim and by-claim random vectors form a sequence of independent and identically distributed random pairs with each pair obeying some certain dependence or arbitrary dependence structure. Under the assumption of heavy-tailed claims, we derive some asymptotic formulas for ultimate ruin probability. Some simulation studies are also performed to check the accuracy of the obtained theoretical results via the crude Monte Carlo method.
Keywords: ultimate ruin probability; asymptotic behavior; main claim and by-claim; bivariate regular variation